Simian virus 40-transformed human cells that express large T antigens defective for viral DNA replication. - Gish, W R (1987)
Many types of human cells cultured in vitro are generally semipermissive for simian virus 40 (SV40) replication. Consequently, subpopulations of stably transformed human cells often carry free viral DNA, which is presumed to arise via spontaneous excision from an integrated DNA template. Stably transformed human cell lines that do not have detectable free DNA are therefore likely to harbor harbor mutant viral genomes incapable of excision and replication, or these cells may synthesize variant cellular proteins necessary for viral replication. We examined four such cell lines and conclude that for the three lines SV80, GM638, and GM639, the cells did indeed harbor spontaneous T-antigen mutants. For the SV80 line, marker rescue (determined by a plaque assay) and DNA sequence analysis of cloned DNA showed that a single point mutation converting serine 147 to asparagine was the cause of the mutation. Similarly, a point mutation converting leucine 457 to methionine for the GM638 mutant T allele was found. Moreover, the SV80 line maintained its permissivity for SV40 DNA replication but did not complement the SV40 tsA209 mutant at its nonpermissive temperature. The cloned SV80 T-antigen allele, though replication incompetent, maintained its ability to transform rodent cells at wild-type efficiencies. A compilation of spontaneously occurring SV40 mutations which cannot replicate but can transform shows that these mutations tend to cluster in two regions of the T-antigen gene, one ascribed to the site-specific DNA-binding ability of the protein, and the other to the ATPase activity which is linked to its helicase activity.